Interaction of coagulase negative staphylococci with lectins. - Jones, J W (1993)
AIMS--To investigate the reaction of 118 blood culture isolates of coagulase negative staphylococci with a panel of seven lectins. METHODS--The interactions between the bacterial suspensions and lectins from Arachnis hypogaea (peanut agglutinin), Bauhina purpurea, Solanum tuberosum (potato starch), Triticum vulgaris (wheat germ agglutinin), Wisteria floribunda, Concanavalin ensiformis and Limulus polphemus (horse-shoe crab agglutinin) were assayed in microtitre plates incubated for 1 hour at room temperature then left overnight at 4 degrees C. Agglutinating activity was detected by examining the pattern of cell settlement compared with that of the controls. RESULTS--Lectins from Solanum tuberosum, Triticum vulgaris, Concanavalin ensiformis and Limulus polyphemus agglutinated 90% of the strains and displayed 11 agglutination patterns which were unrelated to species, clinical relevance, or antibiotic resistance. Fifty three per cent of the isolates fell into three reaction patterns and the other patterns were represented by nine or fewer strains. Replicate cultures investigated simultaneously gave consistent results, but some strains exhibited variation in agglutination patterns on repeat testing. CONCLUSIONS--Based on these observations lectin agglutination patterns seem to offer a method with potential for strain differentiation among coagulase negative staphylococci. Reproducibility may be improved by the use of biotinylated lectins and growing the coagulase negative staphylococci on defined media. Discrimination can be increased by the inclusion of other reactive lectins.